Pelatihan Design Creative Mug di SMK Pangeran Antasari Labuhan Deli - John John; Surya Darma; Emely Sari Marina Napitupulu (Jurnal Kemitraan Masyarakat, 2024)
According to the definition of American Heritage (2007), design is: "Composing or noting; create," and "formulate a plan." Creative mug design is an activity in making one of the merchendise in terms of supporting a branding activity. SMK Pangeran Antasari is the first school to have a Visual Communication Design (DKV) department in Deli Serdang. Therefore, we took the initiative to provide training that can add insight into the design of students at SMK Pangeran Antasari, especially in the DKV department. Through this training, it can also increase students' creativity and foster an interest in entrepreneurial spirit in them. This training is theoretical and practical directly by involving students to design with the size of the mug given and also do their respective mug press with good guidance. The results of this training were able to design and then apply the design to the coated ceramic mug media that had been provided.